Increasing Impact of Spain on the Equity Markets of Brazil, Chile and Mexico During the Neoliberal Reforms of the 1990s - Rivas, Andres; Verma, Rahul; Rodriguez, Antonio; Albuquerque, Pedro H. (Innovation Journal of Social Sciences and Economic Review, 2023)
The article examines stock index price responses in Brazil, Chile, and Mexico to those in the US, Spain, and four European countries during three sub-periods surrounding the neoliberal reforms of the 1990s: 1988 to 1994, 1995 to 1998, and 1999 to 2004. The methodology is empirical and uses time series analysis, in particular impulse response functions (IRFs) derived using vector autoregression (VAR) models. It finds that equity markets became more interconnected as countries opened to international trade and capital flows and that there was an increasing impact of Spain on Latin American equity markets. Stronger economic linkages (more trade and foreign direct investment) between Spain and these countries, especially in Brazil, seem to explain increased equity market interconnectedness. This study concluded that the adoption of neoliberal reforms significantly enhanced the influence of European, and especially Spanish, equity markets on Latin American markets. This has important implications for understanding the global integration of emerging markets during periods of economic liberalization. However, the study is limited by the general constraints of the VAR methodology, including potential biases due to missing control variables and the selection of subsample periods as historical benchmarks. The study limitations are, in general, the same that apply to the VAR methodology, and in particular, to missing control variables or to possible bias in the selection of the subsample periods used as historical benchmarks. To our knowledge, no other work showed that there was an increasing impact of Spain on Latin American equity markets during the neoliberal reform period by using IRFs and VAR models.
Keywords: Emerging markets; Latin America; Spain; Stock markets interdependence; VAR modeling; Neoliberal reforms